2021
DOI: 10.1007/s40744-021-00297-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Psoriatic Arthritis Management and Communication with Physicians in Australia: Results from a Patient Survey

Abstract: Introduction The objective of this report was to evaluate perceptions of psoriatic arthritis (PsA) treatment and satisfaction with healthcare professional (HCP) communication among patients with PsA in Australia, compared with overall global perceptions. Methods Data were collected via a global and country-specific survey (The Harris Poll; November 2, 2017–March 12, 2018). Eligible patients were ≥ 18 years old, had been diagnosed with PsA > 1 year prior, had seen a rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
3
1
0
Order By: Relevance
“…Furthermore, recall of past office visit discussions differed between patients and dermatologists, highlighting an opportunity to better align patient and physician perceptions of PsO treatment and goals of therapy. These findings are in line with results from the global Harris poll, a web-based survey of patients with PsA, which found that most patients wished for increased communication with their physicians about their disease and treatment goals [ 26 ]. Considering that National Psoriasis Foundation (NPF)–American Academy of Dermatology (AAD) guidelines emphasize the importance of the patient–provider relationship in the care of patients with psoriasis [ 7 ], results from UPLIFT suggest there is an opportunity to improve communication and patient care.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, recall of past office visit discussions differed between patients and dermatologists, highlighting an opportunity to better align patient and physician perceptions of PsO treatment and goals of therapy. These findings are in line with results from the global Harris poll, a web-based survey of patients with PsA, which found that most patients wished for increased communication with their physicians about their disease and treatment goals [ 26 ]. Considering that National Psoriasis Foundation (NPF)–American Academy of Dermatology (AAD) guidelines emphasize the importance of the patient–provider relationship in the care of patients with psoriasis [ 7 ], results from UPLIFT suggest there is an opportunity to improve communication and patient care.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, some patients had discontinued oral or injectable/intravenous treatments because of lack of access or insurance issues. Reasons for discontinuing PsO medications among patients in UPLIFT were consistent with those reported in the Harris poll among patients with PsA [ 26 ]. Also, more than 80% of patients with PsO in UPLIFT believed there was a need for better therapies, which was generally consistent with findings from the Harris poll [ 26 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These data highlight the significant burden of these psychosocial factors on the health-related QoL (HRQoL) in both types of SpA. Furthermore, these patients may be frustrated by delayed diagnoses and a lack of communication with their healthcare providers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%